On the way to autonomous driving: How age influences the acceptance of driver assistance systems. (August 2021) - Günthner, Timo; Proff, Heike
Highlights: Using the TAM, the paper examines the influence of age on the acceptance of driver assistance systems. Perceived ease of use and social norm are most important for 50–59-year olds. Perceived usefulness and trust in technology are most important for 60–69-year olds. Trust in technology is most important for 70–90-year olds. Findings prove that older generations are convinced of automated assistance and are willing to use it. Abstract: Driver assistance systems have the potential to create the basis for future mobility solutions. They enable older generations in need of assistance to maintain their mobility even in the case of physical deficits. Therefore, we conducted a literature review and identified factors that may influence the acceptance of driver assistance systems. Based on the technology acceptance model and other influencing factors, we developed a research model that was validated with the help of a study (n = 227). The results show that, depending on age, there are differences in the acceptance of driver assistance systems and their influencing factors among old and young people. The five determinants of acceptance, perceived usefulness, perceived ease of use and trust in technology are viewed as equally important for all age groups. Differences emerge within the group of older vehicle drivers with varying weighting. For the 50–59 age group, perceived ease of use and social norm are most important, while for the 60–69 age group, perceived usefulness and trust in technology are very important. Among 70–90-year olds, trust in technology is emphasized as most important. Our results show how important it is to increase the confidence of older drivers in age-appropriate driver assistance systems, using target-group-specific advertising and public relations work.